Chemoenzymatic Production and Engineering of Chitooligosaccharides and N-acetyl Glucosamine for Refining Biological Activities - Kumar, Manish; Rajput, Meenakshi; Soni, Twinkle; Vivekanand, Vivekanand; Pareek, Nidhi (Frontiers in Chemistry, 2020)
Chitooligosaccharides (COS) and N-acetyl glucosamine (GlcNAc) are currently of enormous relevance to pharmaceutical, nutraceutical, cosmetics, food, and agriculture industries due to their wide range of biological activities, which include antimicrobial, antitumor, antioxidant, anticoagulant, wound healing, immunoregulatory, and hypocholesterolemic effects. A range of methods have been developed for the synthesis of COS with a specific degree of polymerization along with high production titres. In this respect, chemical, enzymatic, and microbial means, along with modern genetic manipulation techniques, have been extensively explored; however no method has been able to competently produce defined COS and GlcNAc in a mono-system approach. Henceforth, the chitin research has turned toward increased exploration of chemoenzymatic processes for COS and GlcNAc generation. Recent developments in the area of green chemicals, mainly ionic liquids, proved vital for the specified COS and GlcNAc synthesis with better yield and purity. Moreover, engineering of COS and GlcNAc to generate novel derivatives viz. carboxylated, sulfated, phenolic acid conjugated, amino derived COS, etc., further improved their biological activities. Consequently, chemoenzymatic synthesis and engineering of COS and GlcNAc emerged as a useful approach to lead the biologically-active compound-based biomedical research to an advanced prospect in the forthcoming era.